Pengaruh Konsentrasi Ekstrak Kulit Manggis (Garcinia Mangostana L) Sebagai Pereda Rasa Nyeri Pada Mencit Muss Musculus (In Vivo) - Uli Erlian Pratama, Rezza; , drg. Ana Riolina, MPH; , drg. SE Yuletnawati, MDSc (2016)
Pain is a sensory and emotional experience unpleasant and potentially damaging the tissue or describe the damage tissue. Natural analgesic ingredient can be used as an alternative besides using chemicals that have many side effects. Natural ingredients which containing analgesic often used people to suppress the pain of one of them is mangosteen peel. Ethanol extract of mangosteen peel has active substances that can inhibit mediators of pain. Ethanol mangosteen peel extract and mefenamic acid has a general mechanism of pain reduction. Objective: to test the ability of ethanol extract of Garcinia mangostana L. peel as a pain reliever and compare the ability of ethanol extract of Garcinia mangostana L. leather mefenamic acid as a pain reliever. Method: this study used pure laboratory experimental methods with Post-Test Only Controlled Group Design. Male mice Mus musculus 20-30 gr. Shapiro-wilk (n <50) was used to normality data test and ANOVA was used to hypothesis. The value of one way ANOVA test showed that the Sig. (P) between groups was 0.000 to look at the effect of analgesic of mangosteen peel ethanol extract and mefenamic acid to pain in mice using a HOTPLATE method with temperature of 42 o o C. LSD showed there were not a significant difference. 40% of ethanol mangosteen peel extract has the greatest percentage of analgesic (37,30%) and mefenamic acid (36,35%).